Selenium and Sulfur to Produce Allium Functional Crops - González Morales, Susana; Pérez Labrada, Fabián; García Enciso, Ema; Leija Martínez, Paola; Medrano Macías, Julia Rosa; Dávila Rangel, Irma; Juárez Maldonado, Antonio; Rivas Martínez, Erika Nohemi; Benavides Mendoza, Adalberto (2017)
Abstract: Selenium is an element that must be considered in the nutrition of certain crops since its use allows the obtaining of biofortiﬁed crops with a positive impact on human health. The objective of this review is to present the information on the use of Se and S in the cultivation of plants of the genus Allium. The main proposal is to use Allium as specialist plants for biofortiﬁcation with Se and S, considering the natural ability to accumulate both elements in different phytochemicals, which promotes the functional value of Allium. In spite of this, in the agricultural production of these species, the addition of sulfur is not realized to obtain functional foods and plants more resistant; it is only sought to cover the necessary requirements for growth. On the other hand, selenium does not appearintheagronomicmanagementplansofmostoftheproducers. IncludingSandSefertilization as part of agronomic management can substantially improve Allium crop production. Allium species may be suitable to carry out biofortiﬁcation with Se; this practice can be combined with the intensive use of S to obtain crops with higher production and sensory, nutritional, and functional quality. Keywords: nutritional quality; biofortiﬁcation; phytochemicals of Allium; sulfur metabolism; selenium metabolism